Chromatin Preparation from Murine Eosinophils for Genome-Wide Analyses. - Bouffi, C (Methods Mol Biol, 2018)
Dynamic gene expression is a major mechanism that directs hematopoietic lineage commitment and differentiation. Recent advances have revealed an association between chromatin signatures and functional genetic sequences such that these chromatin signatures can be used to predict regulatory elements such as enhancers that may direct lineage differentiation. Our understanding of the genetic elements that regulate eosinophil development is very limited, likely due to the technical challenges in working with a rare complex cell. Herein, we describe protocols to sort mature eosinophils from the bone marrow of mice and to prepare chromatin that can be used for ChIP studies for genome-wide mapping of histone marks and transcription factors in mature eosinophils. Comprehensive epigenomic profiling during critical stages in eosinophil development will ultimately aid in defining the gene regulatory networks necessary to regulate eosinophil production.